Comparing the methods of vertical equating for the math learning achievement tests for junior high school students - Chairun Nisa; Heri Retnawati (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2018)
Developing the students’ mathematical ability needs to be carried out to improve the teaching process. This is very important for continuous education. This study aimed to describe: (1) the characteristics of the mathematics achievement tests for grades VII and VIII; (2) the equity constant of the vertical equating result of the mathematics achievement; (3) the accuracy of the mean mean method, mean and sigma, Haebara characteristics curve, Stocking Lord characteristics curve methods in the vertical equating of the tests for grades VII and VIII. The data were the students’ scores for the Higher Order Thinking tests collected with the anchor test design. The analysis technique utilized was the descriptive quantitative analysis. The findings of the study show that: (1) the learning achievement tests for grades VII and VIII have the difficulty level (location) in the fair category (0.190 and 0.451), and the discrimination index (slope) in the category of good with the mean of 0.700 and 0.633; (2) the vertical equating result shows an equation of Y’ = 0.88X-0.27 with the mean and mean method, Y’ = 0.19X-0.02 with the mean and sigma method, Y’ = 0.38X-0.12 with the Haebara characteristics curve method, and Y’ = 0.57X-0.18 with the Stocking and Lord characteristics curve; (3) the lowest Root Mean Square Different (RMSD) belongs to the mean and mean method, followed by the Stocking and Lord characteristics curve method, mean and sigma method, and the Haebara characteristics curve method.